Beach pebbles as a Learning Media: A Case Study of a Prospective Elementary School Teacher - Kurniati, Ratnah; Rumtutuly, Fransheine (Angstrom Centre of Education, 2025)
This case study examines the understanding of Han (a pseudonym), a prospective elementary school teacher in Universitas Pattimura Southwest Maluku Regency, in three weeks with two two-hour meetings each week. The investigator collected data by giving The Integer Test of Primary Operation and followed by an interview. During the research, it was found that Han's conceptual errors occurred in the addition of positive and negative integers, addition of negative integers, subtraction of positive integers, subtraction of negative integers and subtraction involving both positive and negative integers. These conceptual errors occurred because Han applied the rules of multiplication to addition and subtraction. Moreover, in some cases Han also did not pay attention to the operation in the question. It can be concluded that the use of beach pebbles as learning media followed by intensive course can improve Han's understanding in addition and subtraction of integers.